Conflict, Climate, and Cells: A Disaggregated Analysis - Harari, Mariaflavia; Ferrara, Eliana La (The Review of Economics and Statistics, 2018)
We conduct a disaggregated empirical analysis of civil conflict at the subnational level in Africa over 1997 to 2011 using a new gridded data set. We construct an original measure of agriculture-relevant weather shocks exploiting within-year variation in weather and in crop growing season and spatial variation in crop cover. Temporal and spatial spillovers in conflict are addressed through spatial econometric techniques. Negative shocks occurring during the growing season of local crops affect conflict incidence persistently, and local conflict spills over to neighboring cells. We use our estimates to trace the dynamic response to shocks and predict how future warming may affect violence.